1991
DOI: 10.1254/jjp.55.161
|View full text |Cite
|
Sign up to set email alerts
|

Forskolin preferentially dilates the afferent arteriole in the canine kidney.

Abstract: ABSTRACT-Intrarenal infusion of forskolin (0.2,ug/kg/min) in anesthetized dogs increased renal blood flow (RBF) and glomerular filtration rate (GFR) to the same degree but did not change the mean arterial pressure or heart rate. Forskolin also increased urine flow and urinary sodium excretion. The proportional increases in RBF and GFR may result from a preferential action of forskolin to dilate the afferent arteriole.The role of adenosine 3'5'-cyclic monophosphate (cAMP) as a second messenger of hormone-or dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Studies in the resistance vessels of the dog kidney have shown that ET‐1 contracts both afferent and efferent arterioles 10 and that forskolin stimulates the accumulation of cAMP in the isolated afferent arteriole and preferentially dilates the afferent arteriole. 11,12 However, FE Na during NKH477 infusion in the presence of ET‐1 was still lower than that in the absence of ET‐1. Therefore, NKH477 does not seem to inhibit the tubular action of ET‐1.…”
Section: Discussionmentioning
confidence: 94%
“…Studies in the resistance vessels of the dog kidney have shown that ET‐1 contracts both afferent and efferent arterioles 10 and that forskolin stimulates the accumulation of cAMP in the isolated afferent arteriole and preferentially dilates the afferent arteriole. 11,12 However, FE Na during NKH477 infusion in the presence of ET‐1 was still lower than that in the absence of ET‐1. Therefore, NKH477 does not seem to inhibit the tubular action of ET‐1.…”
Section: Discussionmentioning
confidence: 94%
“…The inhibitory effect of forskolin on the contractions of the uterine rings from rats at 16 days of gestation was found to involve the activation of adenylyl cyclase, the adenosine triphosphate-dependent potassium channels and, to a greater extent, calcium-dependent potassium channels [106]. Moreover, intrarenal infusion of forskolin in anesthetized dogs was reported to cause natriuresis with increasing renal blood flow and glomerular filtration rate, which is due to the ability of forskolin to preferentially dilate the afferent arterioles [107]. Eye: Topical ocular administration of 1% forskolin suspension in rabbits, monkeys and human volunteers, who were free from eye disease, was reported to lower the intraocular pressure as a result of a reduction of the net aqueous flow without significant change in outflow facility [108][109][110][111][112].…”
Section: Forskolinmentioning
confidence: 99%